On the Emergence of Russian-South African Business Links. Allan Bowe, Faberge’s Business Partner - GORELIK Boris Moiseevich (Ученые записки Института Африки Российской академии наук)
Allan Bowe, a Cape-born entrepreneur in the Russian Empire, has not been mentioned in literature on the history of Russian-South African contacts. However, his long business partnership with Carl Fabergé should be considered in this context, primarily because it took place when Russia and the territories that are now part of South Africa, apparently, had no trade relations yet.